Public Chaos: Alleged Fatwa on Boycotting and the Fear of Missing Out on Israeli Products in Indonesia - Husna, Nurul; Irfan, Andi Farahdhiba; Juliandi, Budi; Herlambang, Saifuddin; Fadhlunasyifa, Fadhlunasyifa (AHKAM : Jurnal Ilmu Syariah, 2025)
The following text presents a synopsis of the abstract. As the conflict between Israel and Palestine intensifies, the Indonesian Ulama Council (MUI) has issued a fatwa that has generated controversy in various mass media, particularly on social media platforms. The objective of this study is to examine whether the "fatwa" issued by the Indonesian Ulama Council (MUI) constitutes a legitimate threat against Israeli products or a misinterpretation of the fatwa within the community. The research method employed is qualitative, with a descriptive-analytical approach. The secondary data set comprises social media platforms, including Instagram, Twitter, and YouTube, as well as websites relevant to the author's research. The primary data was obtained through interviews with various stakeholders, including consumers, MUI members, pro-Palestinian activists, and digital communication experts. The results indicated that misinterpretations of the fatwa led to public disorder, characterized by ambiguity in public perception, social pressures encouraging boycott conformity, and exacerbated consumer confusion due to digital misinformation. This research highlights the importance of religious literacy and the need to establish information authority within the digital landscape. Abstrak Seiring memanasnya konflik antara Israel dan Palestina, Majelis Ulama Indonesia (MUI) mengeluarkan fatwa yang menuai kontroversi di berbagai media massa, khususnya media sosial. Tujuan penelitian ini adalah untuk mengkaji apakah fatwa yang dikeluarkan oleh Majelis Ulama Indonesia (MUI) tersebut hanya sekadar ancaman bebas terhadap produk Israel atau merupakan kesalahpahaman terhadap fatwa tersebut di tengah masyarakat. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif-analitis; data sekunder meliputi media sosial seperti Instagram, Twitter, YouTube, dan situs web yang terkait dengan penelitian penulis; dan data primer diperoleh melalui wawancara dengan berbagai pemangku kepentingan, meliputi konsumen, anggota MUI, aktivis pro-Palestina, dan pakar komunikasi digital. Hasil penelitian menunjukkan bahwa terjadi kesalahpahaman mengenai fatwa yang menimbulkan kekacauan di ruang publik, yang berujung pada ambiguitas persepsi publik terhadap fatwa tersebut, tekanan sosial yang mendorong konformitas dalam aksi boikot, serta peran misinformasi digital yang memperparah kebingungan konsumen. Penelitian ini menyoroti pentingnya literasi agama dan penguatan otoritas informasi dalam konteks digital.